Treatment completion and quality of life in inpatient alcohol treatment: a secondary observational analysis within a randomized controlled trial in Interior Alaska - Austin Henderson; Robert Rosenman; Carolyn Noonan; Spero M. Manson (Journal of Patient-Reported Outcomes, 2026)
Abstract Background Long-term inpatient alcohol treatment is commonly used to reduce disordered drinking and improve quality of life (QoL). While prior research has identified associations between treatment completion and improved QoL, this relationship may reflect selection: patients with higher baseline QoL may be more likely to complete treatment. Methods Drawing upon data from the Transitions to Recovery (TTR) study, a randomized controlled trial conducted among patients exiting acute detoxification in Interior Alaska, we examined whether baseline psychosocial functioning differed between completers and non-completers, and whether completers experienced better QoL outcomes at a six-month follow-up. Psychosocial functioning was screened at intake using the Client Status Review (CSR); health-related QoL was measured at the six-month follow-up using the EQ-5D-5L. Results We found no significant differences in baseline psychosocial functioning between completion groups on four CSR measures, and CSR scores did not predict treatment completion. At follow-up, treatment completers had significantly higher EQ-5D utility scores (utility index 0.81 vs. 0.73, p = 0.04), with fewer reported problems in mobility and usual activities, though not in anxiety/depression. The association was attenuated and no longer significant after adjustment for covariates. Conclusions Baseline psychosocial functioning did not predict treatment completion, and the higher quality of life observed among completers was concentrated in physical functioning rather than in anxiety or depression. This association did not survive adjustment for covariates or a censored-regression specification. Because health-related QoL was not measured at baseline, we cannot rule out that pre-existing differences in physical functioning facilitated completion rather than completion producing these gains. Under an assumption of sustained benefit, the observed utility difference implies 0.40–0.75 QALYs over a 5–10 year horizon, which would place residential treatment well within conventional cost-effectiveness thresholds. The economic case for such treatment is generally made in these terms, and our findings show how that case rests on a causal interpretation that follow-up data without a quality-of-life baseline cannot support.